How the venetian blind percept emerges from the laminar cortical dynamics of 3D vision - Cao, Yongqiang; Grossberg, Stephen (Frontiers in Psychology, 2014)
The 3D LAMINART model of 3D vision and figure-ground perception is used to explain and simulate a key example of the Venetian blind effect and show how it is related to other well-known perceptual phenomena such as Panum's limiting case. The model shows how identified neurons that interact in hierarchically organized laminar circuits of the visual cortex can simulate many properties of 3D vision percepts, notably consciously seen surface percepts, which are predicted to arise when filled-in surface representations are integrated into surface-shroud resonances between visual and parietal cortex. The model describes how monocular and binocular oriented filtering interacts with later stages of 3D boundary formation and surface filling-in in the lateral geniculate nucleus (LGN) and cortical areas V1, V2, and V4. It proposes how interactions between layers 4, 3B, and 2/3 in V1 and V2 contribute to stereopsis, and how binocular and monocular information combine to form 3D boundary and surface representations. The model suggests how surface-to-boundary feedback from V2 thin stripes to pale stripes enables computationally complementary boundary and surface formation properties to generate a single consistent percept, eliminate redundant 3D boundaries, and trigger figure-ground perception. The model also shows how false binocular boundary matches may be eliminated by Gestalt grouping properties. In particular, a disparity filter, which helps to solve the Correspondence Problem by eliminating false matches, is predicted to be realized as part of the boundary grouping process in layer 2/3 of cortical area V2. The model has been used to simulate the consciously seen 3D surface percepts in 18 psychophysical experiments. These percepts include the Venetian blind effect, Panum's limiting case, contrast variations of dichoptic masking and the correspondence problem, the effect of interocular contrast differences on stereoacuity, stereopsis with polarity-reversed stereograms, da Vin